EARTH’S ELECTROMAGNETIC FIELD ITS PROTECTIVE SYSTEM (Modern American Journal of Medical and Health Sciences, 2025)
Space weather refers to the effects of solar activity – particularly solar storms – throughout the heliosphere, the vast region of space influenced by the Sun, extending out far beyond Pluto. Within this region, charged particles and radiation from the Sun interact with planetary magnetospheres, ionospheres and atmospheres. Conclusion.The Earth's electromagnetic field is an essential component of our planet's natural defense system. Understanding and preserving this invisible shield is crucial for the future of life and technology on Earth.